The use of 3D modeling to determine the parameters of surgical intervention for pulmonary tuberculosis - E. A. Borodulinа; A. V. Kolsаnov; P. V. Rogozhkin; A. A. Mаnukyan (Туберкулез и болезни лёгких)
The clinical experience demonstrates the importance of 3D modeling when planning surgical intervention in patients with pulmonary tuberculosis. The 3D model was built up based computed tomography data using Avtoplan software with plug-ins for segmentation of the lung, pathological foci, vascular structures, and bronchial tree. The data obtained during 3D modeling allowed us to plan surgery and the data were fully confirmed during the operation. The 3D model with color mapping reveals syntopy, which is extremely difficult to determine using standard computed tomography and allows the wider use of minimally invasive endoscopic surgical interventions.